ANALISIS MANAJEMEN PEMBINAAN ATLET SEPAK TAKWRAW PPLP RIAU - januarlis januarlis; Caska Caska; Hasnah Faizah AR (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2021)
Coaching is one of the things that must be done in PPLP because coaching is one of the key successes of PPLP. The existence of high coaching can be one of the capital for PPLP to achieve the expected goals. In order to uphold the coaching, coaching management is needed based on the theories reflected in management functions which consist of planning, organizing, implementing, and monitoring carried out to determine and achieve predetermined goals through the use of human resources and other resources. This research is a type of qualitative research, which is research that tends to deal with research problems that require exploration, where knowledge of the problem is still limited, about a detailed understanding of central phenomena. With data collection techniques carried out with interviews, observations, and documentation. Data processing procedures are carried out by informing checking tringulation techniques, as well as data checking. The results showed, 1) the planning of the coaching management work program has been carried out well, this is evident from the management of athlete coaching which is arranged for short and long term activities, in the implementation of the management of athletes that have been prepared when giving training materials can be implemented as when the management plan for athlete coaching is mutually agreed upon.2) the management of coaching management has been well established this as in the division of tasks and responsibilities in accordance with the decree issued by Dispora, 3) the execution of duties and responsibilities of human resources in charge of the implementer has been able to carry out the responsibilities properly, 4) supervision of the implementation of management management of this guidance has been carried out well, because supervision has been carried out by the leadership both directly and indirectly.